Rapid differentiation between Livestock-Associated and Livestock-Independent Staphylococcus aureus CC398 Clades (2013)
ABSTRACT: Staphylococcus aureus clonal complex 398 (CC398) isolates cluster into two distinct phylogenetic clades based on singlenucleotide polymorphisms (SNPs) revealing a basal human clade and a more derived livestock clade. The scn and tet(M) genes are strongly associated with the human and the livestock clade, respectively, due to loss and acquisition of mobile genetic elements. We present canonical single-nucleotide polymorphism (canSNP) assays that differentiate the two major host-associated S. aureus CC398 clades and a duplex PCR assay for detection of scn and tet(M). The canSNP assays correctly placed 88 S. aureus CC398 isolates from a reference collection into the human and livestock clades and the duplex PCR assay correctly identified scn and tet(M). The assays were successfully applied to a geographically diverse collection of 272 human S. aureus CC398 isolates. The simple assays described here generate signals comparable to a whole-genome phylogeny for major clade assignment and are easily integrated into S. aureus CC398 surveillance programs and epidemiological studies.